Effects of Working Memory and Gloss Type on L2 Text Comprehension and Incidental Vocabulary Learning in Computer-Based Reading. (14th October 2016) - Varol, Burcu; Erçetin, Gülcan
Abstract: Current computer technologies can provide resources for the reader to employ both lexical and topic-level knowledge through glosses. As the reader is engaged in processing the text, s/he can easily access definitions of words or get more information about the topic through hyperlinks. However, there is little consensus regarding the effects of these resources especially on reading comprehension. Given the role of working memory (WM) in reading comprehension, the effects of these text resources may be mediated by WM capacity. As such, the current study, through a between groups experimental design, aims to compare the performance of low-knowledge readers on vocabulary and recall measures when they are exposed to glosses providing lexical information versus topic-level information. It also aims to examine whether WM mediates the effects of gloss content. Upon determining the participants⿿ WM capacity through a backward digit span task, they were randomly assigned to one of the experimental groups, which were exposed to an expository text with either vocabulary glosses or topic-level glosses or to the control group which received no glosses. After reading the text, the participants were given recall and vocabulary measures. Findings yield a significant relationship between WM and reading comprehension regardless of treatment condition and immediate positive effects of glosses on incidental vocabulary learning.